2021
DOI: 10.3126/jist.v26i1.37840
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potency of Copper(I) Complexes Against a Range Cancer Cell Lines: A Review

Abstract: The copper(I) complexes of N,N-diimine, N,O- and/or N, S-bidentate systems perform significant dose-dependent anticancer activity toward various cell lines viz. MCF-7, LNCap, PSN-1, A431, BxPC3, H157, A2780, HeLa, MDA-MB231, MGC-803 etc. The copper(I) complexes can cross the cellular plasmalemma that results in the accumulation of copper ion  in the cancer cells, exhibit significant anticancer effect and overcome the multidrug resistance because these can slightly induce the DNA cleavage as a result of limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…A previous study has demonstrated that interactions between transcription factor 4 (TCF4) and β-catenin are responsible for the transcription of several tumor-related genes, including c-Myc and cyclin D1, and that they play crucial roles in tumorigenesis and the development of different types of cancer, including esophageal, colorectal, and pancreatic cancers . As an essential element of the human body, copper maintains the vitality of cell mitochondria and promotes cell proliferation . Recent studies have shown that the concentration, uptake, transport, and excretion of copper by related transporters increase in colorectal cancer tissues. , An example of these transporters is the solute carrier family 31 member 1/copper transporter 1 (SLC31A1/CTR1), which has an extracellular copper binding domain and is considered to be the main transporter of copper ions into cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has demonstrated that interactions between transcription factor 4 (TCF4) and β-catenin are responsible for the transcription of several tumor-related genes, including c-Myc and cyclin D1, and that they play crucial roles in tumorigenesis and the development of different types of cancer, including esophageal, colorectal, and pancreatic cancers . As an essential element of the human body, copper maintains the vitality of cell mitochondria and promotes cell proliferation . Recent studies have shown that the concentration, uptake, transport, and excretion of copper by related transporters increase in colorectal cancer tissues. , An example of these transporters is the solute carrier family 31 member 1/copper transporter 1 (SLC31A1/CTR1), which has an extracellular copper binding domain and is considered to be the main transporter of copper ions into cells.…”
Section: Introductionmentioning
confidence: 99%
“…12 As an essential element of the human body, copper maintains the vitality of cell mitochondria and promotes cell proliferation. 13 Recent studies have shown that the concentration, uptake, transport, and excretion of copper by related transporters increase in colorectal cancer tissues. 14,15 An example of these transporters is the solute carrier family 31 member 1/copper transporter 1 (SLC31A1/CTR1), which has an extracellular copper binding domain and is considered to be the main transporter of copper ions into cells.…”
Section: ■ Introductionmentioning
confidence: 99%